IN VITRO ASSESSMENT OF ANTIOXIDANT, PHYTOCHEMICAL AND NUTRITIONAL PROPERTIES OF EXTRACTS FROM THE LEAVES OF OCIMUM GRATISSIMUM (LINN) - Igbinosa, Etinosa O.; Uzunuigbe, Edwina O.; Igbinosa, Isoken H.; Odjadjare, Emmanuel E.; Igiehon, Nicholas O.; Emuedo, Oke A. (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The antioxidant, phytochemical and nutritional properties of acetone, methanol and aqueous extracts of the leaves of Ocimum gratissimum (Linn) were investigated to evaluate the therapeutic and nutritional potential of the leaves of this plant. The antioxidant of the plant extracts were assessed against 1,1-Diphenyl-2-picrylhydrazyl (DPPH) and 2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) and ferric reducing agent. Total phenolics, flavonoids, flavonols and proanthocyanidins were determined to assess their corresponding effect on the antioxidant activity of this plant. The extracts exhibited DPPH and ABTS.+ radical scavenging activities, which was comparable to butylated hydroxytoluene (BHT). The phytochemical screening revealed the presence of alkaloids, tannins, saponin, steroids, cardiacglycoside, flavonoid, terpenoids and phenol. The proximate analysis confirms that the leaves contain appreciable amount of ash, crude protein, lipids, fibre and carbohydrates. The macro and micro elements and constituents revealed that the leaves contain significant amount of sodium, potassium, calcium, magnesium, iron, zinc, phosphorus, copper, nitrogen, and manganese. This study shows that the leaf can be used as a therapeutic agent and justifies its application in folkloric medicine.